2008
DOI: 10.1063/1.3006332
|View full text |Cite
|
Sign up to set email alerts
|

Direct hydrogen gas generation by using InGaN epilayers as working electrodes

Abstract: We report on the growth and exploitation of InGaN epilayers as a photoelectrochemical cell (PEC) material for direct generation of hydrogen by splitting water using photoelectrochemical hydrolysis. Under white light illumination, a drastic dependence of the photocurrent density on the In content was observed. Direct hydrogen gas generation by splitting water was accomplished using an n-type InxGa1−xN epilayer with a relatively high In content (x∼0.4) as a working electrode. This demonstration of hydrogen gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 14 publications
1
62
0
1
Order By: Relevance
“…InGaN alloys have been found to fulfill these criteria and are, therefore, a potential candidate as a photoelectrode. [13][14][15][16][17][18][19][20] In the present study we focus on criteria (i) and (ii) and the materials properties of interest are, therefore, the band gap and band alignments.…”
Section: Alloys Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…InGaN alloys have been found to fulfill these criteria and are, therefore, a potential candidate as a photoelectrode. [13][14][15][16][17][18][19][20] In the present study we focus on criteria (i) and (ii) and the materials properties of interest are, therefore, the band gap and band alignments.…”
Section: Alloys Ofmentioning
confidence: 99%
“…Furthermore, alloys of InN and GaN have recently attracted interest for use in multijunction photovoltaic devices [10][11][12] and as photoelectrodes for water splitting. [13][14][15][16][17][18][19][20] In photochemical water splitting, the InGaN semiconductor absorbs sunlight and thereby produces electrons and holes, which drives the water-splitting reaction. Successful photoelectrode materials must fulfill at least the following three criteria: (i) The band gap must be such that a significant fraction of the solar spectrum is absorbed; (ii) the conduction band (CB) and valence band (VB) must straddle the redox potential of hydrogen and water; and (iii) the material must be corrosion resistant.…”
Section: Alloys Ofmentioning
confidence: 99%
“…Experimentally, single crystalline In x Ga 1-x N nanowires with compositions up to x = 0.4~0.5 have been realized. 16 Although the InGaN alloy is a very promising water splitting material, only a few studies have been reported [17][18][19] with no studies on nanowire geometries.One dimensional nanostructures have been demonstrated to be efficient in photoelectrochemical (PEC) cell and photovoltaic cell applications because they can decouple the directions of light absorption and charge carrier collection. [20][21] When the life time of the minority carrier is short, the minority carrier can recombine in bulk before it reaches the semiconductor/electrolyte junction.…”
mentioning
confidence: 99%
“…Group III-nitride compound semiconductors exhibit a direct energy bandgap encompassing nearly the entire solar spectrum. Apart from being stable in photocatalytic environment, [24][25][26] InGaN possesses an additional advantage over other known photocatalysts in that its bandgap can be tuned to straddle the water redox potentials over a large portion of the solar spectrum, namely, ultraviolet, visible, and near-infrared. 27,28 Figure 1 shows the band alignments of InGaN alongside other commonly used photocatalyst materials, depicting the band edge potential for water splitting up to ∼50% indium incorporation.…”
mentioning
confidence: 99%